Analisis Kinerja Rantai Pasok Komoditas Ternak dan Daging Sapi Menggunakan Metode Supply Chain Operation Reference - Rakha Izzatur Rahman; Tasya Aspiranti; Umari Abdurrahim Abi Anwar (Bandung Conference Series: Business and Management, 2024)
Abstract. Companies operating in the livestock sector need to understand productivity, efficiency and fast service, by implementing good Supply Chain. . This research aims to analyse and find out how supply chain performs at CV XYZ, one of the cattle fattening companies in Bandung Regency. Analysis of the Company's supply chain performance is measured using the Supply Chain Operation Reference (SCOR) method. This research is descriptive quantitative and uses case study research methods. Interviews, Documentation, and direct observations were carried out for actual data collection. The results of measuring CV XYZ's supply chain performance using the SCOR method are as follows: Value perfect order fulfillment (POF) 94%, mark order fulfillment cycle time (OFCT) 76 day, and, value cost of goods sold (COGS) 61%, Abstrak. Perusahaan yang bergerak dibidang peternakan perlu pemahaman mengenai produktivitas, efisiensi, dan pelayanan yang cepat, dengan pengimplementasian konsep Rantai Pasok yang baik Penelitian ini bertujuan untuk menganalisis serta mengetahui bagaimana kinerja rantai pasok di CV XYZ salah satu perusahaaan penggemukan sapi yang ada di Kabupaten Bandung. Analisis kinerja rantai pasokan Perusahaan dikur menggunakan metode Supply Chain Operation Reference (SCOR). Penelitian ini bersifat deskriptif kuantitatif dan menggunakan metode penelitian studi kasus. Wawancara, dokumentasi, dan observasi langsung dilakukan untuk pengumpulan data aktual. Hasil pengukuran kinerja rantai pasok CV XYZ menggunakan metode SCOR adalah sebagai berikut: Nilai perfect order fulfillment (POF) 94%, nilai order fulfillment cycle time (OFCT) 76 hari, dan, nilai cost of goods sold (COGS) 61%,